Rett's Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1987)
The sleep and respiratory patterns associated with this disorder have been studied in 11 females aged 2 through 15 years at the Methodist Hospital, Houston, Tx.